Efektivitas Penanganan Keluhan Ganti Rugi Pengadaan Tanah Melalui Omnichannel Communication Assistant (OCA) di Direktorat Jenderal Pengadaan Tanah dan Pengembangan Pertanahan - Riani Djangkaru; Izzatusholekha; Muhammad Yasifa Rizky Prasetya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Handling public complaints is an important indicator in assessing the quality of public services, including land acquisition and compensation services. This study aims to analyze the effectiveness of handling land acquisition compensation complaints through the Omnichannel Communication Assistant (OCA) at the Directorate General of Land Acquisition and Land Development. This study uses a descriptive method with a qualitative approach. Data were obtained through observations during internships as OCA administrators, interviews with complaint service managers, and documentation of complaint ticket data for the period January - December 2025. The results showed that there were 236 complaint tickets received through the OCA. The majority of complaints submitted by the public related to information regarding land acquisition procedures, Compensation Money, and the status of compensation payments. The research findings indicate that the OCA plays a role in facilitating public access to submit complaints and obtain information quickly. In addition, the OCA assists the communication process between the public and relevant agencies in the land acquisition process. However, some complaints still require document verification and cross-agency coordination so that the resolution process cannot be carried out entirely through the OCA system.